Students’ Motivation on The Implementation of MBKM at English Course STIKES Bhakti Husada Mulia Madiun - Lidia Deviga (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Merdeka Belajar-Kampus Merdeka (MBKM) is a policy from the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) that provides students with the flexibility to study outside their study programs or home campuses. The policy aims to enhance competence, prepare graduates for the workforce, and develop self-potential through various programs, while fostering students' interests and motivation in learning. Since it is a relatively new policy, research regarding its implementation and impact is still highly needed. This study aims to: (1) Explore the perceptions of Medical Record students regarding the implementation of the Merdeka Belajar-Kampus Merdeka Program in English learning at the Medical Record Department of STIKES Bhakti Husada Mulia Madiun, (2) Explore the motivation of Medical Record students in English learning to participate in the Merdeka Belajar-Kampus Merdeka Program at the Medical Record Department of STIKES Bhakti Husada Mulia Madiun. The sample of this study consisted of 35 Medical Record students at STIKES Bhakti Husada Mulia Madiun who participated in the MBKM program. Data were collected using questionnaires and interviews. The results indicated several factors influencing students to participate in the MBKM program, which include: (1) Intrinsic Factors: Improvement of soft skills and hard skills, (2) Extrinsic Factors: Career prospects (obtaining a job), praise, and recognition/awards. Medical Record students at STIKES Bhakti Husada Mulia Madiun have participated in the MBKM program, which has been successfully implemented and proven highly beneficial. Through the MBKM Program, students receive learning support, including valuable experience, better personal growth, improved English proficiency, optimal learning, and significant advancement. The ability of the MBKM Program to motivate students can have a positive impact on their future career growth and academic success.